Understanding the Roles of NiOx in Enhancing the Photoelectrochemical Performance of BiVO4 Photoanodes for Solar Water Splitting. Issue 9 (23rd October 2018) - Zhang, Mengyuan; Antony, Rajini P.; Chiam, Sing Yang; Abdi, Fatwa Firdaus; Wong, Lydia Helena
Abstract: Solar water oxidation is considered as a promising method for efficient utilization of solar energy and bismuth vanadate (BiVO4 ) is a potential photoanode. Catalyst loading on BiVO4 is often used to tackle the limitations of charge recombination and sluggish kinetics. In this study, amorphous nickel oxide (NiO x ) is loaded onto Mo‐doped BiVO4 by photochemical metal–organic deposition method. The resulting NiO x /Mo:BiVO4 photoanodes demonstrate a two‐fold improvement in photocurrent density (2.44 mA cm −2 ) at 1.23 V versus reversible hydrogen electrode (RHE) compared with the uncatalyzed samples. After NiO x modification the charge‐separation and charge‐transfer efficiencies improve significantly across the entire potential range. It is further elucidated by open‐circuit photovoltage (OCP), time‐resolved‐microwave conductivity (TRMC), and rapid‐scan voltammetry (RSV) measurements that NiO x modification induces larger band bending and promotes efficient charge transfer on the surface of BiVO4 . This work provides insight into designing BiVO4 ‐catalyst assemblies by using a simple surface‐modification route for efficient solar water oxidation. Abstract : Bending the rules : Nickel oxide (NiO x ) loading on BiVO4 photoanode demonstrates a twofold improvement in photocurrent density as compared with the uncatalyzed one. NiO x modification increases both the charge separation and the charge transfer efficiency significantly, which is attributed to larger band bending and promoted charge transfer at the surface of BiVO4 .